CLUSTERING SUNDANESE CULTURAL ARTICLES ON GOOGLE SCHOLAR: A BIBLIOMETRIC REVIEW - Zaelani, Iwan Ridwan; Budiana, Muhammad (Lembaga Penelitian Universitas Pasundan, 2024)
This study aims to analyze the bibliometric characteristics of articles on Google Scholar indexed Sundanese Culture published in 2016-2021 which were accessed in June 2022. Methods: We conducted a bibliometric analysis and published content in the Google Scholar database. Results: Based on the specified protocol, 219 articles about Sundanese culture over the last 6 years met the inclusion criteria. The frequency of articles is spread across 195 national and international journals with the use of Indonesian language articles 153 articles (70%) and 67 articles (30%) using English. Three ranks of affiliated institutions that are productive in publishing articles on the theme of Sundanese culture, namely Padjadjaran University (39 articles), Universitas Pendidikan Indonesia (21 articles) and Universitas Islam Negeri Sunan Gunung Djati (21 articles). Conclusion: Over the last 6 years scientific publications on the theme of Sundanese culture have provided an overview of the dynamics and value factors of local wisdom identity and cultural preservation in the aspects of art, language, tourism development, character education and cultural and religious synergy between Sundanese and Islam. In terms of various scientific backgrounds and/or study programs, researchers see that the field of communication studies is the most productive